Immunological features of parvovirus infection in different pregnancy periods. - N. P. Bondarenko; W. P. Lakatoch; P. W. Lakatoch (Medičnì Perspektivi, 2018)
Parvovirus infection in pregnant women caused the development of immunopathological reactions.129 infected pregnant women and 16 women with physiological pregnancy in the 1st, 2nd and 3rd trimesters were examined. The functional state of neutrophils (Nph) and monocytes (Mc) of peripheral blood was investigated, parameters of cellular and humoral immunity and cytokine profile of serum of pregnant women were studied. In infected pregnant women in different periods of gestation as compared with pregnant women of control groups there were observed 1) an increase of index of phagocytosis Nph and Mc against the background of reducе of their absorption capacity and increasing NBT-activity with a decrease of reserve capacities of phagocytes; 2) an activation of the cellular immunity with an increase of helper mechanisms of the immune response; 3) a reliable increase of IgM level in serum in different periods of pregnancy; 4) a reliable increase of the content of IFN-γ, FNP-α, IL-2, IL-8 inserum against the background of a slight decrease in the level of anti-inflammatory IL-10. The largest deviations from the control indicators were recorded in the 1st trimester of pregnancy.